Identification and Laboratory Fungicides Screening of the Pathogenic Fungus of Stem Spot of Pitaya (Hylocereus spp.) Stems. (17th May 2022) - Luo, Hui; Guo, Kun; Shang, Xueying; Peng, Lei; Peng, Zhijun; Jin, Jilin; Wang, Bin; Zhang, Xingwu
Abstract : In this study, the pathogenic fungus of stem spot disease of pitaya ( Hylocereus spp.) stems was identified by isolation and purification, pathogenicity test, morphological characteristics, and analysis of rDNA-ITS sequences. The results turned out that the rDNA-ITS sequences of the H1 strain showed 100% of identity with Botryosphaeria dothidea, indicating that the pathogenic fungus of stem spot disease of pitaya stems was Botryosphaeria dothidea . Meanwhile, the H1 strain was then used as a reference strain to screen some commercial fungicides. The bioassay test results indicated that prochloraz had an obvious inhibitory effect on Botryosphaeria dothidea with the EC50 value of 0.0798 μ g/mL. Our study could provide a theoretical basis for the effective control method of stem spot disease of pitaya.